First report of Monoeca in Argentina, with description of two new species (Hymenoptera: Apidae) - Torretta, Juan Pablo; Roig-Alsina, Arturo (Journal of Melittology, 2016)
Two new species of the oil-collecting bee genus Monoeca Lepeletier & Audinet-Serville (Apidae: Tapinotaspidini) are described and figured from females and males captured in northeastern Argentina. The two new species here described, Monoeca armata Torretta & Roig-Alsina, new species, and M. puchella Torretta & Roig-Alsina, new species, are easily distinguished from each other by the color of the integument, the wings, and the pilosity. Their relationships to already described species of the genus are discussed. Monoeca were the only genus of Tapinostaspidini not known to occur in Argentina. The flower records and the study of the pollen scopal loads corroborate the association of these oil-collecting bees with plants of the family Malpighiaceae.